Hubungan Faktor Risiko Dental Ergonomi dengan Keluhan Subjektif Musculoskeletal Disorders (MSDs) pada Dental Assistant: Hubungan Faktor Risiko Dental Ergonomi dengan Keluhan Subjektif Musculoskeletal Disorders (MSDs) pada Dental Assistant - Dhidit Kresno Waskito; Sutrisno Sutrisno; Aryani Widayati; Siti Sulastri (Dental Therapist Journal, 2021)
One of the hazards in dentistry is dental ergonomic. A working problem that can be caused by ergonomic hazards is Musculoskeletal Disorders (MSDs). The dental assistant is one of the jobs that have a risk for the occurrence of abnormalities in the musculoskeletal system. Based on the preliminary study on dental assistants that work in Pontianak City showed that 85% of people had musculoskeletal complaints on the legs, 71,4% had complaints on the calf, and 57,1% had complaints on the shoulder and upper back. The aim of this research is to find out the correlation between risk factors of dental ergonomics and subjective complaints of Musculoskeletal Disorders (MSDs) on dental assistants. The type of this research was a quantitative study with an analytical observational approach using a cross-sectional design. The research was conducted in Pontianak City in August 2021. The population of this research is 48 respondents and the samples were chosen using the total sampling technique. The instrument that used in this research were collected from the risk factors of dental ergonomics and Nordic Body Map (NMB) questionnaires which were later analyzed using Kendall's tau-b test. The result of this research is risk factors of dental ergonomics in the low category is 54,20%. The subjective complaints of Musculoskeletal Disorders (MSDs) in the low category is 68,80%. Based on Kendall's tau-b test showed that P. Value is 0,601 > 0,05 it means that there is no correlation between risk factors of dental ergonomics and subjective complaints of Musculoskeletal Disorders (MSDs). The conclusion of this research is there is no correlation between risk factors of dental ergonomics and subjective complaints of Musculoskeletal Disorders (MSDs) on dental assistants. For further research is expected to examine other risk factors that can cause subjective complaints of Musculoskeletal Disorders (MSDs). Salah satu unsur bahaya dalam dunia kedokteran gigi adalah dental ergonomi. Masalah kerja yang dapat ditimbulkan akibat bahaya ergonomi adalah Musculoskeletal Disorders (MSDs). Pekerjaan dental assistant merupakan salah satu pekerjaan yang memiliki risiko untuk terjadinya keluhan pada sistem musculoskeletal. Hasil studi pendahuluan pada dental assistant yang bekerja di wilayah Kota Pontianak menunjukkan bahwa 85% responden mengalami keluhan musculoskeletal pada bagian kaki, 71,4% pada bagian betis, dan 57,1% pada bagian bahu dan punggung atas. Tujuan penelitian ini adalah untuk mengetahui hubungan antara faktor risiko dental ergonomi dengan keluhan subjektif Musculoskeletal Disorders (MSDs) pada dental assistant. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan observasional analitik menggunakan rancangan cross-sectional. Penelitian ini dilakukan di Kota Pontianak pada bulan Agustus 2021. Populasi dalam penelitian ini adalah 48 responden dan pengambilan sampel menggunakan teknik total sampling. Instrumen dalam penelitian ini menggunakan kuesioner faktor risiko dental ergonomi dan kuesioner Nordic Body Map (NBM). Analisis data menggunakan uji Kendall’s Tau-B. Hasil dari penelitian ini adalah faktor risiko dental ergonomi berada pada kategori rendah (54,20%). Keluhan subjektif Musculoskeletal Disorders (MSDs) berada pada kategori rendah (68,80%). Hasil analisis data menunjukkan nilai P. Value sebesar 0,601 > 0,05 sehingga tidak terdapat hubungan antara faktor risiko dental ergonomi dengan keluhan subjektif Musculoskeletal Disorders (MSDs). Kesimpulan dari penelitian ini adalah tidak terdapat hubungan yang bermakna antara faktor risiko dental ergonomi dengan keluhan subjektif Musculoskeletal Disorders (MSDs) pada dental assistant. Penelitian selanjutnya diharapkan dapat mengkaji faktor-faktor risiko lain yang dapat menyebabkan keluhan subjektif Musculoskeletal Disorders (MSDs).